Act of creation : the founding of the United Nations : a story of superpowers, secret agents, wartime allies and ennemies, and their quest for a peaceful world - Schlesinger, Stephen C. ([Cambridge]: Westview Press, 2003)
"Stephen C. Schlesinger"